Learning Transition from Covid-19 Pandemic to Post Pandemic Era: EFL University Students’ Perspective - Sisimetrika Katleyana; Soni Mirizon; Machdalena Vianty (Indonesian Journal Of Educational Research and Review, 2023)
Following a more than two-year closure due to the COVID-19 pandemic, schools are gradually reopening. The pandemic significantly changed the learning spectrum and school systems when compared to pre-pandemic times. Each student's journey is different, though, due to the personal circumstances that require adjustment to a new environment, each student's transition from online to offline learning is unique. Several studies have been conducted to examine the transition from offline to online, but the transition from online to offline has gotten less attention. Research on students' experiences of transitioning from online learning to offline was conducted to 4 selected students based on several considerations. Narrative experiences which focused on the perspectives of university students in transitioning their online to offline learning was a subject of this research therefore a qualitative design was used. Bridges transition model was adopted as the framework of this study. After conducting semi-structured interviews, the information obtained from the interview transcripts was divided into various coding systems in order to examine the insights. It was discovered that everyone who participated felt differently about the switch to offline learning. In the end, some people perceived the change negatively while others did not. Due to the various challenges, they encountered in both online and offline learning, participants had varying opinions of the learning transition.Â